Materials from Lucas et al. (2025) "The impact of regional-scale upper mantle heterogeneity on glacial isostatic adjustment in West Antarctica" ... - Lucas, Erica M.; Gomez, Natalya; Wilson, Terry (Federated Research Data Repository / dépôt fédéré de données de recherche, 2025)
Data associated with the publication, including sea level change, geoid change, radial displacement, west-east tangential displacement, and south-north tangential displacement. Output data is included for 12 Seakon GIA simulations in total. Seakon GIA simulations are completed using the ICE-125, ICE-25, and ICE-FUT ice models with the 1D_WAIS, CONT, REG_P, and REG_S viscosity models. ...